2021
DOI: 10.1111/jcal.12612
|View full text |Cite
|
Sign up to set email alerts
|

Distance learning perceptions during the coronavirus outbreak: Freshmen versus more advanced students

Abstract: Background The outbreak of the novel coronavirus (COVID‐19) at the beginning of 2020 forced most higher education institutions to shift immediately from traditional learning to distance learning and emergency remote teaching (ERT). Objectives This research aimed to capture the authentic sounds of this unusual learning experience from the field while it was still fresh and to explore congruence with existing models of online learning success factors. We also aimed to examine the differences between freshman stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…In addition, the university student population faced high levels of stress and anxiety, mainly caused by the closure of universities and the adoption of distance learning [28,29], and this impact was even bigger on freshmen [30] who were not able to manage the ability to regulate the emotions related to their studies because of the novelty of their studies. Conversely, older students tended to be more confident and reported higher scores in online learning readiness [31,32].…”
Section: Introductionmentioning
confidence: 88%
“…In addition, the university student population faced high levels of stress and anxiety, mainly caused by the closure of universities and the adoption of distance learning [28,29], and this impact was even bigger on freshmen [30] who were not able to manage the ability to regulate the emotions related to their studies because of the novelty of their studies. Conversely, older students tended to be more confident and reported higher scores in online learning readiness [31,32].…”
Section: Introductionmentioning
confidence: 88%
“…A plethora of research papers has appeared that have intended to gain insight into the various aspects of ERT. Most of these papers deal with the urgent question of transitioning from face-to-face to emergency online learning (Aranyi et al, 2022;Vargas Barquero et al, 2022;Marshall et al, 2020;Yeigh & Lynch, 2020), the relationship between COVID-19 and remote teaching (Alvarez, 2020;Arefi, 2021;Bacsa-Bán, 2022;Donham et al, 2022;Herrmann, 2020;Schrenk et al, 2021;Toquero, 2020), instructor and student perspectives on remote course delivery (Castañeda-Trujillo & Jaime-Osorio, 2021;Chen et al, 2022), as well as student and teacher perceptions, experiences and attitudes to the unconventional for them mode of education (Baruth et al, 2021;Butic Reyes, 2021;Civelek et al, 2021;Gürler et al, 2020;Hussein et al, 2020;Ironsi, 2022;Juárez-Díaz & Perales, 2021;Martin et al 2021;Melnychenko & Zheliaskova, 2021;Ozfidan et al, 2021;Pylypenko & Kozub, 2021;Valizadeh & Soltanpour, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because the starting students missed all traditional face-to-face introduction sessions by the universities, and were also unable to build up their network of peers due to distancing regulations. Baruth et al (2021) found wellknown benefits of distance learning, like flexibility and personalized learning pace. Nevertheless, the findings revealed that ERT posed challenges and difficulties, mainly concerning the readiness of students and instructors for this form of teaching and learning.…”
Section: Cdifferences To Traditional Teachingmentioning
confidence: 99%